Coordinated monitoring and control method of deposited layer width and reinforcement in WAAM process. (November 2021) - Wang, Yiming; Xu, Xingwang; Zhao, Zhuang; Deng, Wenxiang; Han, Jing; Bai, Lianfa; Liang, Xianglong; Yao, Jianyong
Abstract: Wire arc additive manufacturing (WAAM) has been used extensively in metal manufacturing and other fields because of its low cost and high efficiency. In the manufacturing process, WAAM technology is often unable to be further applied due to issues such as component dimensional accuracy, layered morphology, and metallurgical defects. To overcome these problems, online monitoring and process control of the welding are necessary. Based on the monitoring of weld width and reinforcement, a regression network for extracting the global information of molten pool is proposed, and an active disturbance rejection control (ADRC) is designed to adjust the welding current. To the best of our knowledge, this is the first time to realize the coordinated monitoring and control of the width and reinforcement of the deposited layer in the WAAM process. Experiments show that the method can obtain satisfactory molten pool width and reinforcement control accuracy, which provides a feasible way for monitoring and control the weld shape in the WAAM welding process.